AKULTURASI DAN AKOMODASI BAHASA TOLAKI DENGAN BAHASA BUGIS DIKECAMATAN UNAAHA KABUPATEN KONAWE - Iin Fantri Wahid (Jurnal Akrab Juara, 2019)
This research was conducted in Unaaha sub-district of Konawe regency. The approach used in this research was descriptive qualitative by conducting in-depth interviews and observations involved to informants as primary data collection technique. Through the technique of determining informants facilitated and obtained by 17 informants. While the secondary data obtained from the district office in the form of population data and library search. Data were analyze through qualitative descriptive.The result of this research shows that acculturation and accomodation of Tolaki language and Bugis language in Unaaha sub-district of Konawe regency occurs on the scope of the family, school(among peers), and in buying and selling activity. Acculturation actiors and language accomodation are old age (adults) as well as adolescent. While the factors that cause the acculturation and accomodation of Tolaki language with Bugis language in Unaaha district is due to open society attitude and social contact.